The portrayal of violence against women in the films made by Carlos Sigiuon Reyna. - Balsamo, Ethel E. (2002.)
This study deals with gender analysis on the portrayal of violence against women in the films made by Carlos Siguion Reyna. It aims to (1) identify the role of women on the portrayal of violence against women in the films made by Carlos Siguion Reyna, (2) to describe the portrayal of violence against women in the films made by Carlos Siguion Reyna, (3)to explain the portrayal violence against women in the films made by Carlos Siguion Reyna. The twelve films of Carlos Siguion Reyna were briefly presented to aid for further understanding of the study. Different roles of women portrayed in the films were enumerated and explain briefly into their portrayal. Violence against women were categorized into physical, sexual, and emotional abuse. Finally, a gender analysis was used to assess the portrayal of violence against women in the films of Carlos Siguion Reyna. In this study, daata were gathered through self-analysis of some ten films of Carlos Siguion Reyna with the help of some film reviews of his films. Violence against women is evident in the films of director and it comes in many forms, be it physical, sexual, and emotional abuse. Patriarchy, women seen as sex objectt are some of the factors that contributed to the violence toward women and it happens in most social groups and all income levels. The ideas and images of women in reality are reinforced in the mass media on which people model their behavior and attitudes. Thus, indeed there is a relationship between the social condition of women in reality and the portrayal of violence against women in films.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Carlos Sigioun Reyna -- Films; Violence against women -- Films